KELANJUTAN EKSISTENSI KERAJINAN BAMBU DESA GINTANGAN DENGAN MODEL MATEMATIKA SEBAGAI DAYA TARIK PARIWISATA BANYUWANGI - Auda Nuril Zazilah; I Putu Sudhyana Mecha (Universitas Muhammadiyah Semarang, 2021)
Bamboo woven craft of Gintangan Village is one of the tourist attractions in Banyuwangi which has become a characteristic of Gintangan Village, Banyuwangi Regency and should be preserved. By interviewing the managers, sellers, craftsmen and the young generation, several real conditions were obtained which were then interpreted in the form of mathematical models and systems of differential equations. Furthermore, by analyzing the critical point of the system of differential equations, the condition of the existence of the Gintangan Village bamboo woven craft is obtained. The critical point showed that by providing the birth number that was greater than death number, the number of incoming residents was greater than the number of outgoing residents, and the conversion number of non-craftsmen to craftsmen was greater than number of craftsmen who decided to stop, it was found that at one time the number of non-craftsmen was little than the number of craftsmen. This situation has a good impact on the existence of bamboo woven craft of Gintangan Village in Banyuwangi.